ANALISIS KELAYAKAN INVESTASI AKTIVA TETAP PADA INDUSTRI RUMAH TANGGA MOSHIMOSHI CAKE DI SAMARINDA - Abbas, Fitria (EKONOMIA, 2013)
The domestic industry is basically for profit (profit), to support its business activities, the company needs to think about the investment policies, thus one of the factors that affect customer requirements for products of goods and services as well as provide satisfaction and efficiency are the fixed asset investment.Issues to be discussed is "Is Fixed Assets Investment (oven) At Home Industry Moshimoshi Cake in Samarinda Worth? '.The purpose of this study to determine viable or not Fixed Assets Investment (oven) At Home Industry Moshimoshi Cake in Samarinda.Basic theory used is financial management, financial reporting, fixed assets, depreciation, particularly investment theory using the data of 2010, 2011, and 2012, investment was determined using the Payback Period and Net Present Value (NPV) as an analytical tool.Formulated the hypothesis that the author is: "fixed asset investment (oven) in the domestic industry Moshimoshi Cake feasible".The results of efforts Household Industrial Moshimoshi Cake using acceptable payback period analysis to speed time return the funds 1 month 3 days, and the analysis of the Net Present Value (NPV) may be accepted at Rp. 276 319 598.Based on the analysis and discussion, the conclusions of this study are as follows:Using the Payback Period, then known investment is acceptable to speed the return of funds is time 1 month 3 days and the Net Present Value (NPV) investment of Rp acceptable. 276 319 598.Thus the hypothesis put forward previously stated that the fixed asset investment (oven) at home industry Moshimoshi Cake feasible ". accepted.